Impact of a basic mathematics course on the performance of college students in algebra subject (2020)
A common problem for universities is the lack of knowledge and mathematical skills of new students because this deficiency creates difficulties in their studies throughout their career, which can cause their dropout. The aim of this paper is to describe the impact of a basic mathematics course on the performance of college student in algebra subject. This is a 32-hour course which is developed in 16 sessions in parallel to the algebra classes and is mainly offered to students: a) identified with low performance on mathematics component of national highschool test, and b) remitted by the subject teacher. The main findings are: a) the pass rate for students who attended to more than half of the sessions of the course if 95%, and b) the average grade of the subject tends to increase as with the attendance level to the course of the students. Consequently, these results lead to the conclusion that the course has a positive effect on the students' performance.